TEKNIK PEMBONGKARAN TUMBUHAN INVASIF Acacia nilotica (L) Willd. Ex. Del DENGAN TIRFOR DI TAMAN NASIONAL BALURAN JAWA TIMUR - Zakaria Basari (Jurnal Penelitian Hasil Hutan, 2012)
The objective of this research is to study the effectiveness of semi mechanical control of Acacia nilotica (L) Willd. Ex. Del using tirfor in Baluran National Park in 2009. The results showed that the 75 trees were trunked using tirfor but 15 tree maually. The average productivity of each was 3,59 trees per hour and 0,5 trees per boar. The averages operational cost were Rp 5,277/ trees and Rp 16,666/trees. The soil bas been displaced with an average rate of 1%/ m per trees and 6,252 / mi per trees for semi mechanic and manual. Respectively the volume of 1,5587 m has been produced from 75.A. nilotica lry using tirfor and 0,3 m from manually. All of wood produced bas not been utilized yet.